Potential limits of capacitive deionization and membrane capacitive deionization for water electrolysis. Issue 13 (2nd September 2019) - Kim, Y.-H.; Tang, K.; Chang, J.; Sharma, K.; Yiacoumi, S.; Mayes, R.T.; Bilheux, H.Z.; Santodonato, L.J.; Tsouris, C.
ABSTRACT: Water electrolysis can hinder the operation of capacitive deionization (CDI) and membrane CDI (MCDI). This study is aimed at investigating the overpotential limits of CDI and MCDI (OP-MCDI) for water electrolysis and desalination performance. For sodium chloride concentrations of ~28, 460 ppm, MCDI with mesoporous carbon electrodes could be operated at up to 2.4 V without water electrolysis, and the salt-adsorption capacity of the OP-MCDI system at 2.4 V was about two times greater than that of the MCDI at 1.2 V. This study offers an opportunity to extend the applicability of conventional CDI and MCDI systems for desalination of low-salinity solutions.